The impacts of some plant protection chemical OCPs on two crustacean species \(Daphnia magna\) and \(Moina macrocopa\) - Tran Thi, Thu Huong; Nguyen Xuan, Tong; Le Hung, Anh; Le Van, Hau (Vietnam Journal of Marine Science and Technology, 2022)
DDT (Dichloro-diphenyl-trichloroethane) and chlordane are the organochlorine pesticides (OCPs) dangerous to human health and easily accumulate in biological tissues, used to control insects in crops, livestock and house protection. This study aimed to evaluate the toxicity of DDT, cis (alpha-chlordane), and trans (gamma-chlordane) on the growth of two crustaceans species Daphnia magna (D. magna) and Moina macrocopa (M. macrocopa) after 24 h and 48 h. Each test concentration selected 9 individuals of each species and repeated 4 experimental times, the study results showed that the 50% lethal concentration (LC50) of D. magna and M. macrocopa when exposed to DDT for 24 h were 20.8 μg.L-1 and 13.5 μg.L-1, respectively; after 48 h the value decreased to only 4.8 μg.L-1 and 1.7 μg.L-1. Similarly, LC50 values of cis (alpha-chlordane) on 2 species after 24 h exposure were 12.4 μg.L-1 and 11.8 μg.L-1, respectively; after 48 h were 4.6 μg.L-1 and 4.9 μg.L-1. The calculation results of LC50 when exposed to trans (gamma-chlordane) of D. magna and M. macrocopa after 24 h are 17.6 μg.L-1 and 12.4 μg.L-1, respectively; after 48 h, it decreased to 3.8 μg.L-1 and 3.7 μg.L-1 (p < 0.05). The results of the acute toxicity assessment also indicated that M. macrocopa was more sensitive to toxicity than D. magna with the same test conditions.